A NEW APPROACH FOR EVALUATING THE RANKINE CYCLE THROUGH ENTROPY GENERATION - Karakurt, A. Sinan; Gunes, Umit (YILDIZ TECHNICAL UNIV, 2019)
Increasing oil prices, the growing demand for energy, the adoption of new regulations for greenhouse gases and other harmful particulate emissions, as well as political instabilities and crises have necessitated the design of more efficient and environmentally-friendly plants. This paper presents a useful combination of mean cycle irreversibility (MCI) for thermodynamically optimizing the Rankine cycle using the MCI as the currently proposed criterion. The thermal irreversibilities and physical size of a system are evaluated together using the criterion that aims to minimize the ratio of the thermal irreversibilities or exergy destruction to a specified size that is characterized as the difference between the maximum and the minimum specific volumes of the cycle. The analyses consider the effects of different boiler-outlet or turbine-inlet pressures and temperatures, different condenser pressures, and different isentropic efficiencies on cycle performance. The results show that increasing the inlet temperature for a constant turbine-inlet pressure increases the MCI and increasing the turbine-inlet pressure at a constant inlet temperature decreases the MCI. With boiler pressure at 500 kPa, the boiler temperature increases from 500K to 600K, the MCI value increases nearly seven-fold, and thermal efficiency increases from 14% to nearly 16%. Also, the results show that the criterion gives more beneficial information to designers and engineers in terms of exergy destruction for designing more environmentally friendly and smaller thermal systems.
Keywords: Rankine Cycle; Entropy Generation; Exergy Density; PERFORMANCE ECOP OPTIMIZATION; ECOLOGICAL COEFFICIENT; HEAT-ENGINE; POWER; MINIMIZATION; EFFICIENCY; SYSTEMS; SIZE; Thermodynamics